Transmission of infection from non-isolated patients with COVID-19 to healthcare workers. Issue 4 (December 2020) - Basso, T.; Nordbø, S.A.; Sundqvist, E.; Martinsen, T.C.; Witsø, E.; Wik, T.S.
Summary: Insufficiently protected healthcare workers (HCWs), defined as high-risk contacts of patients with coronavirus disease 2019 (COVID-19), are routinely quarantined. This study evaluated the transmission of infection from a symptomatic patient with COVID-19 to 60 HCWs exposed at ≤2 m for ≥15 min or during aerosol-generating procedures. Following ≥106 unique high-risk contacts, none of the HCWs tested positive for severe acute respiratory syndrome coronavirus-2 RNA or developed antibodies. The HCWs reported adherence to basic infection control procedures. These results are in accordance with other reports, and should reassure HCWs and further stimulate broader evaluation of the foundation for the current practice of home quarantining non-symptomatic HCWs.